MANAJEMEN PENINGKATAN MUTU PADA FAKULTAS TARBIYAH DAN TADRIS IAIN BENGKULU (Perspektif Teori Total Quality Management) - Samsudin Samsudin; Kurniawan Kurniawan (Nuansa : Jurnal Studi Islam dan Kemasyarakatan, 2017)
The result  of the research could  be concluded the management for improving quality at Tarbiyah and  Tadris Faculty  IAIN Bengkulu in perspective theory of Total Quality  Management (TQM) could  be implemented at Tarbiyah and Tadris Faculty IAIN Bengkulu. They were relevant and significant with principles or values of Total Quality Manage- ment, because there were the same philosophy, principles, values and the supporting elements. The management strat- egies were fixed continuosly, formed by the quality of standard, given service,  defended the relation to the customer, increased the  human resourches by educational training, organization changing that  based on institution statusquo, empowerment of employee in activities. The implementation of the strategies can be effective. These can be proved by the results of the research relevant with the indicators. The effective of strategies were improved the lecturer of quality, improved the lecturer’s dicipline, an officer improved service  for the student, increased the facility. The processing of improving quality could  be meazured by the quality standard, external customers especially, for the student in order to be easy consulted, given the facility for student in order to give evaluation of the lecturer work by information academic system (SIAKAD), box advice  and questionnaires